Elliptic Filter Based Noninvasive Blood Pressure Analyze with LabVIEW - Kaya, Duygu; Türk, Mustafa; Kaya, Turgay (Fırat University, 2017)
The blood in the vein is called blood pressure or tension. It depends on the amount of blood pumped by the heartand the resistance of the vessels to this flow and the flexibility of the arterial walls. Very low values thanoptimum blood pressure and very high values than normal blood pressure are important. With this aim,Noninvasive Blood Pressure Analyze with LabVIEW offers an insight into us. LabVIEW is a graphicalprogramming language that uses a Dataflow model instead of sequential lines of text code. LabVIEW runsprinciple of Data flow programming that allows multiple operations to work in parallel. So, designers spend lesstime than a text based programming language. Application areas such as signal processing, image processing andData analysis are available. In this paper, LabVIEW- based Noninvasive Blood Pressure Analyze (NIBP) usingdifferent Data and to obtain systolic/diastolic pressure. As a result of this, the current data are divided intooptimum blood pressure, normal blood pressure and prehypertension